Chemical composition and microbiota changes across musk secretion stages of forest musk deer - Xu, Zhongxian; Li, Feng; Liu, Qian; Ma, Tianyuan; Feng, Xiaolan; Zhao, Guijun; Zeng, Dejun; Li, Diyan; Jie, Hang (Frontiers in Microbiology, 2024)
Forest musk deer is the most important animal for natural musk production, and the musk composition changes periodically during musk secretion, accompanied by variation in the com-position of deersymbiotic bacteria. In this study, the dynamic changes to correlated chemical composition and the microbiota across musk secretion periods (prime musk secretion period, vigorous musk secretion period and late musk secretion period) were investigated by integrating its serum testosterone level in different mating states. Results showed that the testosterone level, musk composition and microbiota changed with annual cycle of musk secretion and affected by its mating state. Muscone and the testosterone level peaked at vigorous musk secretion period, and the microbiota of this stage was distinct from the other 2 periods. Actinobacteria, Firmicutes and Proteobacteria were dominant bacteria across musk secretion period. PICRUSt analysis demonstrated that bacteria were ubiquitous in musk pod and involved in the metabolism of antibiotics and terpenoids in musk. "Carbohydrates and amino acids", "fatty acids and CoA" and "secretion of metabolites" were enriched at 3 periods, respectively. Pseudomonas, Corynebacterium, Clostridium, Sulfuricurvum were potential biomarkers across musk secretion. Actinobacteria and Corynebacterium have predicted roles in the synthesis of muscone and etiocholanone during musk secretion, which required further validation.